The Relation Between Learning and Stimulus–Response Binding. - Frings, Christian; Foerster, Anna; Moeller, Birte; Pastötter, Bernhard; Pfister, Roland (Psychological Review, 2024)
Perception and action rely on integrating or binding different features of stimuli and responses. Such bindings are short-lived, but they can be retrieved for a limited amount of time if any of their features is reactivated. This is particularly true for stimulus–response bindings, allowing for flexible recycling of previous action plans. A relation to learning of stimulus–response associations suggests itself, and previous accounts have proposed binding as an initial step of forging associations in long-term memory. The evidence for this claim is surprisingly mixed, however. Here we propose a framework that explains previous failures to detect meaningful relations of binding and learning by highlighting the joint contribution of three variables: (a) decay, (b) the number of repetitions, and (c) the time elapsing between repetitions. Accounting for the interplay of these variables provides a promising blueprint for innovative experimental designs that bridge the gap between immediate bindings on the one hand and lasting associations in memory on the other hand.